State of the art and future directions in assessing the quality of life in rare and complex connective tissue and musculoskeletal diseases - Trieste, Leopoldo; Cannizzo, Sara; Palla, Ilaria; Triulzi, Isotta; Turchetti, Giuseppe (Frontiers in Medicine, 2022)
As chronic conditions, rare and complex connective tissue and musculoskeletal diseases (rCTDs) significantly affect the quality of life generating an impact on the physical, psychological, social, and economic dimensions of the patients’ lives, having implications on the family, changing the lifestyle, the interpersonal relationships, etc. Traditionally, measuring the QoL provides valuable information to clinicians and researchers on the impact of the disease, the effect of the medical interventions on the patients, and the quality of care. The QoL affects healthcare services utilization, and predicts morbidities and mortalities, workability, etc.; generic QoL measures and disease-specific QoL measures have been adopted for clinical and economic analysis. the assessment of unmet clinical needs, satisfaction with the treatment and the care, and some characteristics of the disease that strongly matter to the patient could represent valuable dimensions to be considered in the QoL impact assessment as well as measuring the impact of these diseases by considering the perspectives of family members/informal caregivers, for instance considering values, beliefs, experiences, life circumstances, psychological aspects, family relationships, economic issues, changes in social activities, etc. Therefore, tools that consider the individuals’ perspectives in evaluating the QoL in rCTDs are needed. The aim of this work is to better understand the status of QoL metrics used in clinical and economic research for the assessment of the individuals’ perspectives on living with rCTDs. Results: Anxiety & depression, Body image satisfaction, Daily activity, Fatigue, Illness perception, Pain, Personality, QoL, Resilience, Satisfaction with the relationship, Self-management, Sexual QoL, Sleep quality, Social support, Stress, Uncertainty, Work productivity are the main dimensions considered in the included studies. However, “more shadows than lights” can summarize the review’s outcome in terms of PROMs domains covered per each rCTDs. Conclusions: What is missing is the inclusion of the patients’ perspectives in evaluating the QoL in rare diseases? Are there specific metrics for the assessment of the patients’ perspectives? There is a need for future research in specific QoL metrics that takes into consideration the perspective of people living with rare diseases: patients, families, and caregivers.